Planejamento para a conservação de plantas ameaçadas no cerrado brasileiro - Monteiro, Lara de Macedo (2017)
Earth is facing the highest species' extinction rates of its history, and humans are the major stressar. Adding up to this biodiversity crisis, species-rich areas, which also coincide with areas highly transformed by humans (e.g. biodiversity hotspots), are poorly covered by protected areas. ln Brazil this reality is not different. Responsible for harbouring a third of all plant species already classified under a threat category (n= 645), the Brazilian Cerrado has only 8.3% of its area legally protected. ln this biorne, the campos rupestres, a mountaintop grassland ecosystem, stands out for its high number of threatened species currently underrepresented in conservation strategies. ln chapter 1, we aimed at indicating priority areas to secure protection of the threatened plant species from the southern Espinhaço mountains, a region that encampasses large areas of campos rupestres. We found that it is possible to protect, on average, more than 25% of the threatened species' ranges, avoiding sites with extensive use for farming and mining and favouring areas with intensive fire frequency by constraining the management to a relatively small area of only 17% of the region. Conservation plans such as these proposed for campos rupestres represent important opportunities to fulfil the gap existent between research and implementation. However, we do not rule out the need for increasing sophisticated tools that account for the consequences of complex processes threatening biodiversity in the near future ( e.g. clima te change and deforestation) and especially the need for predictive and realistic conservation strategies that anticipate and mitigate their negative effects. Unfortunately, until now we have been relying species protection to a residual system of PAs that provide minimal conservation impact. Thus, in chapter 2 we aimed to select spatial conservation priorites that minimize the risk of deforestation while retaining sites with high plant biodiversity value threatened from climate change in the Brazilian Cerrado. We simulated two ways of spacing out priorities for conservation actions ("time-step action" and "acting now''), and two methods of setting priorities: one that minimizes expected habitat conversion and prioritizes high valuable sites to plant biodiversity at risk from climate change (maximum conservation impact) and another that prioritizes sites based only on their value for plant biodiversity at risk from climate change, regardless their vulnerability to land conversion ("usual approach''). We found that although the scenarios that maximize conservation impact avoided higher amounts of vegetation loss, they prevented least species' range loss. Moreover, the acting now scenarios always performed better in terms of range loss avoided compared to the time-step scenarios under the sarne method of prioritization. Finally, we believe that planning for vegetation loss avoidance is a more conservative strategy because vegetation information is less subjective to any source of bias and is a better surrogate for general biodiversity. We also recommend that acting as soon as possible is always the best strategy to guarantee biodiversity conservation in the Cerrado.